Etnobotani Tumbuhan Obat yang Dijual di Blok Bahan Jamu Pasar Raya I Salatiga - Ananda, Raditya Se'o; Suprihati, Suprihati (Bioscientist : Jurnal Ilmiah Biologi, 2023)
Ethnobotany is a branch of science that studies the correlation between humans and plants. Generally, the basic ingredients for making herbal medicine come from types of medicinal plants. The majority of city residents buy medicinal plants from markets or drug stores. Pasar Raya I Salatiga as a source of meeting the needs of the people of Salatiga City. The aim of this research is to know the types of medicinal plants being sold, knowing the parts of the medicinal plants being sold, knowing the shape of the medicinal plants being sold, knowing how to obtain the medicinal plants being sold, and knowing the agrotechnological engineering actions of one of the medicinal plants being sold. This research is a qualitative descriptive research. This research was conducted with three herbal medicine sellers, three consumers, and three ginger farmers. This research was conducted in August-September 2023. Data collection techniques used semi-structured interviews, observation, literature study and documentation. Data processing with simple statistics. The research results found a total of 92 medicinal plants. The parts of medicinal plants sold include roots (4%), stems (7%), seeds (19%), fruit (16%), flowers (4%), leaves (26%), leaves & flowers (1%), herbs (1%), bark (4%), rhizomes (15%), and tubers (3%). The forms of medicinal plants sold include dry (71%), fresh (17%), dry & fresh (7%), and processed (5%). All medicinal plants are obtained by purchasing. Agrotechnological engineering actions carried out by ginger farmers include applying fertilizer, planting in the right season and scheduling planting.